SPATIAL DISTRIBUTION OF SPECIFIC RUNOFF IN SERBIA BASED ON RAINFALL-RUNOFF RELATIONSHIP - Marko Urošev; Dragoljub Štrbac; Jelena Kovačević-Majkić; Jasna Plavšić; Stanislav A. Yamashkin (Zbornik Radova: Geografski institut "Jovan Cvijić", 2020)
One of the indicators of water potential and water resources is specific runoff. Specific runoff for the whole territory of Serbia was obtained using the exponential relation between depth of runoff Y (mm) and precipitation P (mm). This relation is obtained on the basis of the mean annual amount of precipitation and annual water discharge, namely the depth of the runoff for 69 basins for the period 1961–2010. Coefficient of determination (R²) of relation between the depth of runoff and precipitation is 0.72. The differences between measured and modeled values of specific runoff vary from basin to basin, but at the level of the whole Serbia it is 3.5%. More precisely, the measured specific runoff amounts 5.6 l/s/km2, and the modeled specific runoff is 5.7 l/s/km2. The verification was done by applying the model to 11 large river basins in Serbia. Spatial distribution of the modeled specific runoff is presented by a digital map of specific runoff with pixel resolution 100 × 100 m which enables the estimation of mean annual water discharge in any ungauged basin in Serbia.